Design Parameters for Photovoltaic Power Conversion in Space - Ray, K. A. (IEEE transactions on applications and industry, 1963)
Such design parameters as current, voltage, temperature, and intensity dependency for silicon solar cells are listed. Their relationship to the basic photovoltaic theory is given, and methods for establishing the parameters are described. Other subjects covered are: (1) the solar cell physical characteristics and their interaction with mounting substrate characteristics; (2) typical solar cell panel configuration; (3) the thermal balance problem and typical thermal characteristics such as emissivity and absorptivity; and (4) the ``state of the art'' for power and weight figure-of-merit for space power conversion.